Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

Neoarchean fractionated A-type monzogranites in the Linshan Massif, southern North China Craton: Implications for intra-arc rifting - Kang Li; Hao Deng; Xilin Zhao; Timothy Kusky; Ali Polat; Lu Wang; Junpeng Wang; Ziyu Dong (Precambrian Research, 2026)

Neoarchean tectonic regime of the Eastern Hebei Complex, North China Craton: Constraints from Mafic-Ultramafic rocks in the Zunhua-Shangying ophiolitic Mélange - Ruizhi Wang; Lu Wang; Wenbin Ning; Hao Deng; Timothy Kusky (Precambrian Research, 2026)

Palaeowildfire regimes and their palaeoenvironmental significance during the Middle Jurassic of the Ordos Basin - Jiamin Zhou; Longyi Shao; Timothy P. Jones; Man Huang; Langlang Wang; Xiaotao Xu; Xiaoyun Yan; Jing Lu (Science China Earth Sciences, 2026)

Identifying Ancient Zircon Provenances Using a Domain-Adversarial Neural Network - Mengwei Zhang; Guoxiong Chen; Timothy Kusky; T. Mark Harrison; Lu Wang; Qiuming Cheng (Mathematical Geosciences, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Carbon capture from ArcelorMittal hot briquetted Iron plant using air liquide cryocap™ FG technology – FEED study - Sebastiano Giardinella; Varun Gopalakrishnan; Vincent Gueret; Lindsey Turney; Vincent Lu; Chris Tovee; David Zybko; Marcelo Andrade; Christopher Harris; Pierre-Philippe Guerif; Timothy Henderson; Anderson Morelato; et al. (International Journal of Greenhouse Gas Control, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Field efficacy, adult emergence, and yield evaluation of the corn rootworm transgenic events in Vorceed™ Enlist® corn and SmartStax® PRO hybrid corn against corn rootworms (Coleoptera: Chrysomelidae) - Timothy Mabry; Jeffrey Klever; Christianah Oladoye; Timothy Nowatzki; James Bing; Amit Sethi; Michael Price; Lu Liu (Crop Protection, 2025)

Multi-proxy records of wildfires and climate-vegetation-wildfire interactions during the Middle Jurassic of the Santanghu Basin, northwest China - Jiamin Zhou; Longyi Shao; Timothy P. Jones; Yangyang Huang; Mengran Chen; Yuedong Ma; Jing Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Machine learning in spatiotemporal PM2.5 hotspots analysis for better targeted mitigation strategies - Danni Lu; Alireza Yazdiani; Timothy Fraser; Mohammad Tayarani; H. Oliver Gao (Transportation Research Part D: Transport and Environment, 2025)

Multi-proxy records of wildfires and climate-vegetation-wildfire mechanisms during the Middle Jurassic of the Yili Basin, Northwest China - Jiamin Zhou; Longyi Shao; Timothy P. Jones; Yangyang Huang; Mengran Chen; Jing Lu; Jason Hilton (Global and Planetary Change, 2025)

Putting Regional Fisheries Management Organisations' Climate Change House in Order - Kamal Azmi; Graham Pilling; Johann Bell; Yi‐Jay Chang; Adele Dutilloy; Timothy H. Frawley; Paul Hamer; John Hampton; Quentin Hanich; Tyla Hill‐Moana; Jhen Hsu; Glenn Hurry; et al. (Fish and Fisheries, 2025)
Climate change is expected to have significant impacts on the biology, abundance and distribution of transboundary fish stocks, not only among neighbouring countries within the jurisdictions of regional fisheries management organisations (RFMOs) but also between adjacent RFMOs. Using South Pacific albacore tuna ( Thunnus alalunga ) as a case study, we highlight how RFMOs need to understand the impacts of climate change on transboundary stocks under their purview with greater certainty. We identify four areas of research that should assist RFMOs to adapt their scientific processes—strengthened understanding of changes in the biology of target stocks; enhanced collection of data to support modelling; improved modelling of catch‐per‐unit of effort (CPUE) to better reflect climate change impacts on stock abundance for assessments; and ensuring that scientific advice is adaptive and robust to climate change, including through implementation of tested harvest strategies. Investments in these research areas should enable RFMOs to improve the science underpinning management measures designed to sustain transboundary stocks and increase fishery performance during climate change.

Inverted metamorphic gradient in the Zanhuang nappe/thrust system, north China indicates large-scale thrust stacking in an Archean Orogen - Yating Zhong; Kurt Stüwe; Timothy Kusky; Christoph A. Hauzenberger; Simon Schorn; Lu Wang (Earth and Planetary Science Letters, 2025)

Cenozoic intracontinental tectonics of Mongolia and its climate effects: A synthesized review - Ulambadrakh Khukhuudei; Timothy Kusky; Brian F. Windley; Orolzodmaa Otgonbayar; Lu Wang; Jungsheng Nie; Wenjiao Xiao; Lei Zhang; Xiaodong Song (Earth-Science Reviews, 2024)

Mechanisms of inertinite enrichment in Jurassic coals: Insights from a Big Data-driven review - Jiamin Zhou; Longyi Shao; Timothy P. Jones; Yangyang Huang; Mengran Chen; Haihai Hou; Jing Lu; Jason Hilton (Earth-Science Reviews, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Growth of the Central Orogenic Belt, North China Craton through accretion of different Neoarchean arc terranes: Perspective from the Linshan complex - Ziyu Dong; Hao Deng; Timothy Kusky; Ali Polat; Guanglei Peng; He Zhang; Lu Wang; Junpeng Wang (Precambrian Research, 2024)

Inertinite in coal and its geoenvironmental significance: Insights from AI and big data analysis - Longyi Shao; Jiamin Zhou; Timothy P. Jones; Fanghui Hua; Xiaotao Xu; Zhiming Yan; Haihai Hou; Dongdong Wang; Jing Lu (Science China Earth Sciences, 2024)

Associations of plasma proteomics and age-related outcomes with brain age in a diverse cohort - Ramon Casanova; Keenan A. Walker; Jamie N. Justice; Andrea Anderson; Michael R. Duggan; Jenifer Cordon; Ryan T. Barnard; Lingyi Lu; Fang-Chi Hsu; Sanaz Sedaghat; Anna Prizment; Stephen B. Kritchevsky; et al. (GeroScience, 2024)
Machine learning models are increasingly being used to estimate “brain age” from neuroimaging data. The gap between chronological age and the estimated brain age gap (BAG) is potentially a measure of accelerated and resilient brain aging. Brain age calculated in this fashion has been shown to be associated with mortality, measures of physical function, health, and disease. Here, we estimate the BAG using a voxel-based elastic net regression approach, and then, we investigate its associations with mortality, cognitive status, and measures of health and disease in participants from Atherosclerosis Risk in Communities (ARIC) study who had a brain MRI at visit 5 of the study. Finally, we used the SOMAscan assay containing 4877 proteins to examine the proteomic associations with the MRI-defined BAG. Among N = 1849 participants (age, 76.4 (SD 5.6)), we found that increased values of BAG were strongly associated with increased mortality and increased severity of the cognitive status. Strong associations with mortality persisted when the analyses were performed in cognitively normal participants. In addition, it was strongly associated with BMI, diabetes, measures of physical function, hypertension, prevalent heart disease, and stroke. Finally, we found 33 proteins associated with BAG after a correction for multiple comparisons. The top proteins with positive associations to brain age were growth/differentiation factor 15 (GDF-15), Sushi, von Willebrand factor type A, EGF, and pentraxin domain-containing protein 1 (SEVP 1), matrilysin (MMP7), ADAMTS-like protein 2 (ADAMTS), and heat shock 70 kDa protein 1B (HSPA1B) while EGF-receptor (EGFR), mast/stem-cell-growth-factor-receptor (KIT), coagulation-factor-VII, and cGMP-dependent-protein-kinase-1 (PRKG1) were negatively associated to brain age. Several of these proteins were previously associated with dementia in ARIC. These results suggest that circulating proteins implicated in biological aging, cellular senescence, angiogenesis, and coagulation are associated with a neuroimaging measure of brain aging.

Genesis of Archean to Paleoproterozoic banded iron formations in the North China Craton: Geological and paleoenvironmental implications - Kang Jiang; Junpeng Wang; Timothy Kusky; Ali Polat; Bo Huang; Lu Wang; Shengli Li; Hao Deng; Yaying Peng (Earth-Science Reviews, 2024)

SNX17 Mediates Dendritic Spine Maturation via p140Cap - Qiuyan Cui; Shiqi Liang; Hao Li; Yiqing Guo; Junkai Lv; Xinyuan Wang; Pengwei Qin; Huaxi Xu; Timothy Y. Huang; Youming Lu; Qing Tian; Tongmei Zhang (Molecular Neurobiology, 2024)

To the transition zone and back: Records from diopside exsolution lamellae in chromite from Archean ophiolitic podiform chromitites - Wei Hu; Lu Wang; Timothy Kusky; Tao Chen (Earth and Planetary Science Letters, 2024)

The relationship between wheat yield and sun-induced chlorophyll fluorescence from continuous measurements over the growing season - Jie Zhu; Yuming Yin; Jingshan Lu; Timothy A. Warner; Xinwen Xu; Mingyu Lyu; Xue Wang; Caili Guo; Tao Cheng; Yan Zhu; Weixing Cao; Xia Yao; et al. (Remote Sensing of Environment, 2023)

Characterization of a complex sand-rich gas hydrate reservoir system in the Indian marine continental margin with downhole log and seismic data - Jilin Zhou; Xiujuan Wang; Timothy S. Collett; Sanzhong Li; Zenggui Kuang; Yintao Lu; Wei Deng; Weichao Yan; Jin Qian; Jiapeng Jin (Marine and Petroleum Geology, 2023)

Greener residential environment is associated with increased bacterial diversity in outdoor ambient air - Jennifer N. Styles; Andrey I. Egorov; Shannon M. Griffin; Jo Klein; J.W. Scott; Elizabeth A. Sams; Edward Hudgens; Chris Mugford; Jill R. Stewart; Kun Lu; Ilona Jaspers; Scott P. Keely; et al. (Science of The Total Environment, 2023)

Alpine-style tectonic nappe stacking in an Archean suture zone: Quantitative structural profile places constraints on orogenic architecture - Yating Zhong; Timothy M. Kusky; Lu Wang; Chuanhai Wang; Yaying Peng; Tingting Wang; Chao Yan (Gondwana Research, 2023)

Neoarchean SSZ and MOR ultra-/high-pressure ophiolitic mélanges of the Eastern Hebei Complex, North China Craton: Dynamics of an Archean paleo-subduction zone - Wenbin Ning; Timothy Kusky; Lu Wang; Junpeng Wang; Hao Deng; Bo Huang; Jiannan Meng; Ruizhi Wang; Die Hu; Yaying Peng; Zhiyuan Chen; Weikang Zhang (Earth-Science Reviews, 2023)

Twin Earthquakes Devastate Southeast Türkiye and Syria: First Report from the Epicenters - Timothy M. Kusky; Erdin Bozkurt; Jiannan Meng; Lu Wang (Journal of Earth Science, 2023)

Growth of continental crust in intra-oceanic and continental-margin arc systems: Analogs for Archean systems - Timothy Kusky; Lu Wang (Science China Earth Sciences, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Roots and microbiome jointly drive the distributions of 17 phytohormones in the plant soil continuum in a phytohormone‐specific manner - Yuqiu Lu; Enzhao Wang; Zhiyu Tang; Junpeng Rui; Yanling Li; Zhixi Tang; Weiling Dong; Xiongduo Liu; Timothy S. George; Alin Song; Fenliang Fan (Plant and Soil, 2022)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Dating hypogene iron mineralization events in Archean BIF at Weld Range, Western Australia: insights into the tectonomagmatic history of the northern margin of the Yilgarn Craton - Paul Duuring; João O. S. Santos; Imogen O. H. Fielding; Timothy J. Ivanic; Steffen G. Hagemann; Thomas Angerer; Yong-Jun Lu; Malcolm Roberts; Jinwoo Choi (Mineralium Deposita, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Erratum to: Petrogenesis and Geotectonic Significance of Early-Neoproterozoic Olivine-Gabbro within the Yangtze Craton: Constrains from the Mineral Composition, U-Pb Age and Hf Isotopes of Zircons - Xingfu Jiang; Songbai Peng; Timothy M. Kusky; Lu Wang; Hao Deng (Journal of Earth Science, 2018)

Zircon and Monazite Ages Constraints on Devonian Magmatism and Granulite-Facies Metamorphism in the Southern Qaidam Block: Implications for Evolution of Proto- and Paleo-Tethys in East Asia - Jin Ba; Lu Zhang; Chuan He; Neng-Song Chen; Timothy M. Kusky; Qinyan Wang; Yusheng Wan; Xiaoming Liu (Journal of Earth Science, 2018)

The first record of Ophioleila elegans (Echinodermata: Ophiuroidea) from a deep-sea seamount in the Northwest Pacific Ocean - Dongsheng Zhang; Bo Lu; Chunsheng Wang; Timothy D. O’Hara (Acta Oceanologica Sinica, 2018)

Phosphate starvation response controls genes required to synthesize the phosphate analog arsenate - Qian Wang; Yoon‐Suk Kang; Abdullah Alowaifeer; Kaixiang Shi; Xia Fan; Lu Wang; Jonathan Jetter; Brian Bothner; Gejiao Wang; Timothy R. McDermott (Environmental Microbiology, 2018)
Summary Environmental arsenic poisoning affects roughly 200 million people worldwide. The toxicity and mobility of arsenic in the environment is significantly influenced by microbial redox reactions, with arsenite (As III ) being more toxic than arsenate (As V ). Microbial oxidation of As III to As V is known to be regulated by the AioXSR signal transduction system and viewed to function for detoxification or energy generation. Here, we show that As III oxidation is ultimately regulated by the phosphate starvation response (PSR), requiring the sensor kinase PhoR for expression of the As III oxidase structural genes aioBA . The PhoRB and AioSR signal transduction systems are capable of transphosphorylation cross‐talk, closely integrating As III oxidation with the PSR. Further, under PSR conditions, As V significantly extends bacterial growth and accumulates in the lipid fraction to the apparent exclusion of phosphorus. This could spare phosphorus for nucleic acid synthesis or triphosphate metabolism wherein unstable arsenic esters are not tolerated, thereby enhancing cell survival potential. We conclude that As III oxidation is logically part of the bacterial PSR, enabling the synthesis of the phosphate analog As V to replace phosphorus in specific biomolecules or to synthesize other molecules capable of a similar function, although not for total replacement of cellular phosphate.

Petrogenesis and Geotectonic Significance of Early-Neoproterzoic Olivine-Gabbro within the Yangtze Craton: Constrains from the Mineral Composition, U-Pb Age and Hf Isotopes of Zircons - Xingfu Jiang; Songbai Peng; Timothy M. Kusky; Lu Wang; Hao Deng (Journal of Earth Science, 2018)

Are DXA/aBMD and QCT/FEA Stiffness and Strength Estimates Sensitive to Sex and Age? - Asghar Rezaei; Hugo Giambini; Timothy Rossman; Kent D. Carlson; Michael J. Yaszemski; Lichun Lu; Dan Dragomir-Daescu (Annals of Biomedical Engineering, 2017)

Development of a novel method for the strengthening and toughening of irradiation-sterilized bone allografts - Tarik Attia; Mitchell Woodside; Gagan Minhas; Xing Ze Lu; David S. Josey; Timothy Burrow; Marc Grynpas; Thomas L. Willett (Cell and Tissue Banking, 2017)

Ecophysiological and foliar nitrogen concentration responses of understorey Acacia spp. and Eucalyptus sp. to prescribed burning - Ling Ma; Xingquan Rao; Ping Lu; Shahla Hosseini Bai; Zhihong Xu; Xiaoyang Chen; Timothy Blumfield; Jun Xie (Environmental Science and Pollution Research, 2015)

Fate of arsenate following arsenite oxidation in A grobacterium tumefaciens GW 4 - Qian Wang; Dong Qin; Shengzhe Zhang; Lu Wang; Jingxin Li; Christopher Rensing; Timothy R. McDermott; Gejiao Wang (Environmental Microbiology, 2015)
Summary The fate of arsenate ( As V ) generated by microbial arsenite ( As III ) oxidation is poorly understood. A grobacterium tumefaciens wild‐type strain ( GW 4) was studied to determine how the cell copes with As V generated in batch culture. GW 4 grown heterotrophically with mannitol used As III as a supplemental energy supply as reflected by enhanced growth and increased cellular levels of NADH and ATP . Under low phosphate ( P i) conditions and presence of As III oxidation, up to ∼ 50% of the resulting As V was taken up and found associated with the periplasm, membrane or cytoplasm fractions of the cells. Arsenic was found associated with proteins and polar lipids, but not in nucleic acids or sugars. Thin‐layer chromatography and gas chromatography–mass spectrometry analysis suggested the presence of arsenolipids in membranes, presumably as part of the bilayer structure of the cell membrane and replacing P i under P i‐limiting conditions. The potential role of a P i‐binding protein ( PstS ) for As V uptake was assessed with the His‐tag purified protein. Intrinsic tryptophan fluorescence spectra analysis suggests that PstS can bind As V , but with lower affinity as compared with P i. In early stationary phase cells, the As V : P i ratio was approximately 4.3 and accompanied by an altered cell ultrastructure.

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Zircon Hf isotope of Yingfeng Rapakivi granites from the Quanji Massif and ∼2.7 Ga crustal growth - Nengsong Chen; Songlin Gong; Xiaoping Xia; Hongyan Geng; Lu Wang; Min Sun; Timothy M. Kusky (Journal of Earth Science, 2013)

Genetic variation of single nucleotide polymorphisms identified at the mating type locus correlates with form-specific disease phenotype in the barley net blotch fungus Pyrenophora teres - Shunwen Lu; Michael C. Edwards; Timothy L. Friesen (European Journal of Plant Pathology, 2013)

On the role of dual active margin collision for exhuming the world’s largest ultrahigh pressure metamorphic belt - Lu Wang; Timothy M. Kusky; M. Santosh (Journal of Earth Science, 2012)

Thermal stress responses in the bacterial biosphere of the G reat B arrier R eef sponge, R hopaloeides odorabile - Rachel Simister; Michael W. Taylor; Peter Tsai; Lu Fan; Timothy J Bruxner; Mark L Crowe; Nicole Webster (Environmental Microbiology, 2012)
Summary Marine sponges are diverse, abundant and provide a crucial coupling point between benthic and pelagic habitats due to their high filtration rates. They also harbour extensive microbial communities, with many microbial phylotypes found exclusively in sponge hosts and not in the seawater or surrounding environment, i.e. so‐called sponge‐specific clusters ( SCs ) or sponge‐ and coral‐specific clusters ( SCCs ). We employed DNA (16 S rRNA gene) and RNA (16 S rRNA )‐based amplicon pyrosequencing to investigate the effects of sublethal thermal stress on the bacterial biosphere of the G reat B arrier R eef sponge R hopaloeides odorabile . A total of 8381 operational taxonomic units ( OTUs ) (97% sequence similarity) were identified, affiliated with 32 bacterial phyla from seawater samples, 23 bacterial phyla from sponge DNA extracts and 18 bacterial phyla from sponge RNA extracts. Sublethal thermal stress (31° C ) had no effect on the present and/or active portions of the R. odorabile bacterial community but a shift in the bacterial assemblage was observed in necrotic sponges. Over two‐thirds of DNA and RNA sequences could be assigned to previously defined SCs / SCCs in healthy sponges whereas only 12% of reads from necrotic sponges could be assigned to SCs / SCCs . A rapid decline in host health over a 1° C temperature increment suggests that sponges such as R . odorabile may be highly vulnerable to the effects of global climate change.

Geological features and deformational ages of the basal thrust belt of the miaowan ophiolite in the southern Huangling anticline and its tectonic implications - Xingfu Jiang; Songbai Peng; Timothy M. Kusky; Lu Wang; Junpeng Wang; Hao Deng (Journal of Earth Science, 2012)

Sea-floor metamorphism recorded in epidosites from the ca. 1.0 Ga Miaowan ophiolite, Huangling anticline, China - Junpeng Wang; Timothy M. Kusky; Ali Polat; Lu Wang; Songbai Peng; Xingfu Jiang; Hao Deng; Songjie Wang (Journal of Earth Science, 2012)

Granulite facies metamorphic age and tectonic implications of BIFs from the Kongling Group in the northern Huangling anticline - Yang Cen; Songbai Peng; Timothy M. Kusky; Xingfu Jiang; Lu Wang (Journal of Earth Science, 2012)

New research progress on the pre-Sinian tectonic evolution and neotectonics of the Huangling anticline region, South China - Songbai Peng; Timothy M. Kusky; Hanwen Zhou; Lu Wang; Wei Xiang (Journal of Earth Science, 2012)

Discovery of a sheeted dike complex in the northern Yangtze craton and its implications for craton evolution - Hao Deng; Timothy M. Kusky; Lu Wang; Songbai Peng; Xingfu Jiang; Junpeng Wang; Songjie Wang (Journal of Earth Science, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Molecular characterization and genomic mapping of the pathogenesis-related protein 1 (PR-1) gene family in hexaploid wheat (Triticum aestivum L.) - Shunwen Lu; Timothy L. Friesen; Justin D. Faris (Molecular Genetics and Genomics, 2011)

Application of the modern ophiolite concept with special reference to Precambrian ophiolites - Timothy M. Kusky; Lu Wang; Yildirim Dilek; Paul Robinson; SongBai Peng; XuYa Huang (Science China Earth Sciences, 2011)

Focusing seismic energy along faults through time-variable rupture modes: Wenchuan earthquake, China - Timothy M. Kusky; Abduwasit Ghulam; Lu Wang; Jianguo Liu; Zhongquan Li; Xiao Chen (Journal of Earth Science, 2010)

Geological evolution of Longhushan World Geopark in relation to global tectonics - Timothy M. Kusky; Minghe Ye; Junpeng Wang; Lu Wang (Journal of Earth Science, 2010)

Application of (15NH4)2SO4 to study N dynamics in hoop pine plantation and adjacent native forest of subtropical Australia: the effects of injection depth and litter addition - Kaiwen Pan; Zhihong Xu; Timothy J. Blumfield; Shane Tutua; Manxin Lu (Journal of Soils and Sediments, 2009)

Insights into corn genes derived from large-scale cDNA sequencing - Nickolai N. Alexandrov; Vyacheslav V. Brover; Stanislav Freidin; Maxim E. Troukhan; Tatiana V. Tatarinova; Hongyu Zhang; Timothy J. Swaller; Yu-Ping Lu; John Bouck; Richard B. Flavell; Kenneth A. Feldmann (Plant Molecular Biology, 2009)

Tumor-associated protein SPIK/TATI suppresses serine protease dependent cell apoptosis - Xuanyong Lu; Jason Lamontagne; Felix Lu; Timothy M. Block (Apoptosis, 2008)

Patterns of linkage disequilibrium in the MHC region on human chromosome 6p - Annette Stenzel; Timothy Lu; W. Andreas Koch; Jochen Hampe; Simone M. Guenther; Francisco M. De La Vega; Michael Krawczak; Stefan Schreiber (Human Genetics, 2004)

Percutaneous Delivery of Thalidomide and Its N-Alkyl Analogs - Colleen Goosen; Timothy J. Laing; Jeanetta du Plessis; Theunis C. Goosen; Guang-Wei Lu; Gordon L. Flynn (Pharmaceutical Research, 2002)

Estimating Type B Genetic Correlations with Unbalanced Data and Heterogeneous Variances for Half-Sib Experiments - Peng-xin Lu; Timothy L. White; Dudley A. Huber (Forest Science, 1999)
A statistical approach is proposed for estimating type B genetic correlations with unbalanced data and heterogeneous variances across environments. First, parental GCA (one-half of the parental breeding value) effects are predicted separately for each environment using best linear unbiased prediction (BLUP). Second, predicted parental GCAs are weighted by their prediction accuracies and Pearson correlation between weighted GCAs in two environments is obtained. Third, type B genetic correlation is calculated by dividing the Pearson correlation with the mean products of prediction accuracies. Advantages of this approach include: (1) fixed effects are removed using best linear unbiased estimation (BLUE) so that they less seriously confound genetic effects when data are unbalanced; (2) heterogeneous variances associated with genetic group means are adjusted for during the process of parental GCA prediction; and (3) it is applicable when experimental designs are different in two environments. Numeric comparisons of estimation methods using simulated data of known true genetic parameters indicated that the new approach produces less bias and higher precision when data are highly unbalanced or have high level heterogeneity of variances across environments. For slightly or moderately unbalanced data, the method of Yamada (1962), however, is simpler and yields satisfactory estimates using standardized data. For. Sci. 45(4):562-572.